Inheritance across faiths in Muslim Minahasa families: Legal pluralism and cultural adaptation in Manado, Indonesia - Luntajo, Mohammad Muzwir; Hasan, Faradila (Universitas Islam Indonesia, 2025)
IntroductionInheritance law in Islam traditionally prohibits inheritance between Muslims and non-Muslims. However, in the context of Muslim Minahasa families in Manado, Indonesia, interfaith dynamics within families challenge the strict application of this norm. Local customs emphasize familial unity and communal harmony, which often influence how inheritance is distributed, regardless of religious affiliation.ObjectivesThis study aims to explore how inheritance is distributed in Muslim families of Minahasa ethnicity when religious differences exist among heirs. It seeks to understand how Islamic inheritance law interacts with Minahasa cultural values and whether local customs override religious legal boundaries in favor of social cohesion.MethodThis research adopts a qualitative socio-legal approach, combining fieldwork and document analysis. Data were collected through in-depth interviews with five Muslim Minahasa families in the Lawangirung area of Manado and one mosque official. Additionally, selected inheritance court decisions were analyzed to understand how the legal system responds to interfaith inheritance cases in the local context.ResultsThe findings indicate that Muslim Minahasa families prioritize familial harmony over strict adherence to Islamic inheritance law. In cases where family members have different religions, inheritance is commonly distributed based on mutual agreement and moral obligation rather than formal legal guidance. Religious differences are not viewed as a disqualifying factor. Cultural values such as mapalus (mutual cooperation) and si tou timou tumou tou (the philosophy of living to empower others) play a central role in shaping inheritance practices. The application of wasiat wajibah (obligatory bequest) in court decisions provides a legal mechanism to accommodate non-Muslim heirs without fully departing from Islamic jurisprudence.ImplicationsThis study reveals a form of legal pluralism in which customary norms and religious values coexist and interact. It highlights the importance of cultural context in the interpretation and application of Islamic law. For policymakers, religious authorities, and legal practitioners, the findings offer valuable insight into alternative models of inheritance that prioritize social harmony in multi-religious families.Originality/NoveltyThis research contributes new knowledge to the discourse on Islamic law and legal pluralism by examining inheritance across religious boundaries within a culturally rich and religiously diverse community. It offers an ethnographically grounded understanding of how Minahasa Muslims reconcile Islamic principles with inclusive customary values, thereby promoting a harmonious legal and familial order.